Challenges and advantages of modern rural surgery: an experience of two secondary care centres of rural India - Baruah, Arijit R.; Kalita, Darpana; Baruah, Shyamanta M.; Baruah, Rajib K. (International Journal Of Community Medicine And Public Health, 2024)
Background: Rural surgery refers to the practice of surgery in rural communities and geographically remote areas, facing multiple challenges like limitation of resources and manpower, poverty, multiple co-morbidities and superstitions. Assam has geographical and population diversity with more than 85 percent of rural population. This study was done to analyse the various challenges and advantages faced during surgical practice in two secondary care centres of rural Assam. Methods: This is a retrospective study done from 228 cases which were operated in Teok First Referral Unit and Titabor Sub-Divisional Civil Hospital, both secondary care centres of rural Assam, India between July 2022 to August 2023 by a single surgeon. Inclusion criteria were all patients who were operated following written and informed consent. Patients who opted not to operate and pregnant women were excluded from the study. Data collected were placed in charts and tables and statistical analysis done using IBM statistical package for the social sciences (SPSS) statistics version 2.0. Results: Study population has 46 percent adult male, 51 percent adult female and 3 percent children. 1.3 percent (3 patients) were operated under general anaesthesia, 14.5 under regional anaesthesia and 73.2 percent under local anaesthesia. 11 percent (25 patients) opted not to operate. Challenges were lack of manpower, lack of resources, infection control, fatigue, trust issues and socio-political pressure. Advantages are financial relief, homely environment, better diet and care, community support, avoiding unnecessary referral and better follow-up. Conclusions: Rural surgery can be a boon to modern healthcare if available resources and manpower are properly managed and challenges are overcome.